EFEKTIVITAS PROGRAM PERENCANAAN PEMBANGUNAN DESA DIGITAL ( Studi Kasus di Desa Dlingo Kecamatan Dlingo Kabupaten Bantul ) - Happy Susanto; Mohammad Kus Yunanto; Suryo Ediyono (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
The presence of Law Number 6 of 2014 about Village provides the basis that the village government is required to be able to respond to local demands and aspirations of the interests of the community in the village. One of the important issues in village deliberation and development is the planning aspect. In accordance with the mandate of the law, village development planning requires the active participation of all community groups. Along with the development and demands of the Industrial Revolution 4.0, the village government needs to innovate policies, namely by digitizing development planning. Thus, the community will be able to participate directly and be more active in participating in developing the village. For this reason, this study seeks to find out how effective the implementation of development planning programs is in villages that are famous for their digitalization. The researcher took the case of Dlingo Village as a digital village which has now changed from an underdeveloped area to a rapidly developing village. This study has a qualitative paradigm, which is used as a method to explore and understand the meaning that comes from the case of development planning in Dlingo Village, Dlingo District, Bantul Regency, DIY.